2014
DOI: 10.1038/ki.2014.3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the receptor for advanced glycation end products induces nuclear inhibitor of protein phosphatase-1 suppression

Abstract: The activation of the receptor for advanced glycation end products (RAGE) is involved in the development of diabetic nephropathy. Analysis of protein phosphatase-1 indicated that advanced glycation end products did not affect its expression, but increased its phosphatase activity. Using differential display analysis we previously demonstrated that stimulation of RAGE in podocytes modulates the expression of numerous genes, among others nuclear inhibitor of protein phosphatase-1 (NIPP1). Here we found that sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 68 publications
(108 reference statements)
7
17
0
1
Order By: Relevance
“…Previous work of our group showed that the expression of the nuclear inhibitor of protein phosphatase 1 (NIPP1) was significantly decreased in podocytes of diabetic db/db mice, and as well in vitro in murine podocytes treated with glycated BSA (AGE-BSA) [5]. Similar findings were observed in renal biopsy specimens from patients with DKD [5].…”
Section: Introductionsupporting
confidence: 72%
“…Previous work of our group showed that the expression of the nuclear inhibitor of protein phosphatase 1 (NIPP1) was significantly decreased in podocytes of diabetic db/db mice, and as well in vitro in murine podocytes treated with glycated BSA (AGE-BSA) [5]. Similar findings were observed in renal biopsy specimens from patients with DKD [5].…”
Section: Introductionsupporting
confidence: 72%
“…This inhibition may be a potential therapeutic advantage because local renal proinflammatory processes are important for the development and progression of DN [8,9]. In addition, it has been shown that AGE-BSA activates proinflammatory pathways in other cell systems [22,23,24]. Although clinical studies have suggested that paricalcitol may have advantages over ‘classical' vitamin D3 [25,26], in our in vitro study, vitamin D3 and paricalcitol were equally effective in suppressing the NFκB activation (albeit in some experiments, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…AGEs can induce ectopic calcification in vascular tissues (Pugliese et al ., 2015; Wang et al ., 2012). Activation of the receptor of AGE (RAGE) (Wei et al ., 2013) was recently shown to induce hypertrophy in podocytes (Liebisch et al ., 2014) and calcification in smooth muscle cells (Wang et al ., 2013b). However, the cellular microenvironment in IVDs is very different from that in more highly vascularised tissues, thereby requiring further investigation.…”
Section: Introductionmentioning
confidence: 99%